Service Quality Assessment in PT.Indokemika Jayatama Using INDSERV Scale and Importance-Performance Analysis - Subianto, Eduardus Ivan; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2013)
Everyday, competition in the business landscape is always increasing. In the year 2012, its 25th year of establishment, PT Indokemika Jayatama tries to achieve its goal to become the leading player in the chemicals trading and distribution business. To achieve goal to become leading player, Indokemika needs to better understand market’s perception toward its service quality. This study aimed to achieve that understanding by conducting a market survey, followed by gap analysis in service quality dimensions described by INDSERV scale, which Gounaris introduced in 2005, and focusing the target using Importance-Performance Analysis by Martilla and James (1977). Questionnaires, containing 21 questions to explain B2B service quality attributes, were sent to Indokemika’s active customers. The Performance-Importance Gap Analysis and Importance-Performance Analysis (IPA) Map inferred that Indokemika’s performance of service quality is perceived as lower than customers’ perceived importance. This is showed by the positive gap score with average gap score at 0.302, and 14 attributes dominated by Hard Process and Output Quality dimension of INDSERV scale are above the average gap. The IPA Map then indicates that the quality attribute that needs improvement, which has the third highest gap score, is ‘Look after customer’s interest’ of the Soft Process Quality dimension. Thus, Indokemika should focus improvement in that direction. Keywords: Perceived service quality, INDSERV, Performance-Importance Gap, IPA Map